MENGURAI UNFINISHED BUSINESS: PENDEKATAN GESTALT DALAM REHABILITASI NARKOBA - Wiryo Nuryono; Ildagis Binarsia; Fahmida Qurrotussalwa; Devi Ratnasari (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
Addictive substances such as drugs can be addictive and affect the functioning of the body and central nervous system. If used excessively or not according to the rules, these substances can cause physical and psychological dependence. Effects include stimulation, sedation or changes in perception, mood and behaviour. According to the counselee, drug use can affect the counselee's psychological state, behaviour and outlook on life. The purpose of this scientific journal is to find out the role of Gestalt counselling that can help recovery from drug addiction. The method used in this scientific journal is deductive qualitative with a case study approach. The research subjects are adolescents (users who have the potential of maladaptive behaviour and a distorted perspective of future life influenced by block energy in the past). This scientific journal found two themes, namely the resolution of unfinished business in the past that is related to drug addiction. Thus, Gestalt counselling can help to decipher the counselee's past that has an impact on drug abuse.